Innovative Leadership In Madrasah: Strategies For Improving The Quality Of Religious Education - Ahmad Tantowi; Subaidi Subaidi; Nina Sofiana; Abdullah Ibrahim; Camila Fatah Suroyya (At-Tarbiyat, 2024)
This study explores how madrasah leaders endeavour to improve the quality of religious education through innovative leadership. This research uses a qualitative approach with data collection methods through interviews, documentation and observation. Data analysis began with reviewing all data obtained from various sources, followed by a data reduction process. The condensed data was organised in a structured manner by selecting important points. The research findings show that: The madrasah head adopts a forward-thinking leadership approach, collaborating with other leaders to develop madrasah programmes that focus on learning religious subjects. This aims for students to excel in religious education competitions at district, provincial and national levels; The madrasah principal aims to assist students in managing their time effectively. The impact of this study shows that the innovative leadership implemented by the madrasah principal not only improves the quality of religious education but also equips students with better time management skills, ultimately improving their overall academic performance.